Unusual cutaneous toxicity after prolonged use of Hydroxyurea in polycythemia vera: a case report - Molinari Elisa; Barabino Gianfranco; Arboscello Eleonora; Del Corso Lisette; Bellodi Andrea; Sicbaldi Vera; Favorini Serena; Ghio Riccardo; Balleari Enrico (Journal of Hematology and Oncology Research, 2015)
Hydroxyurea (HU) is commonly used for the long-term treatment of patients with chronic myeloproliferative neoplasms. The drug is usually well tolerated in the large majority of subjects, although systemic and/or localized toxicities have seldom been reported. Here we report a case of unusual cutaneous toxicity due long-term use of HU in a patient with polycythemia vera.
Keywords: Hydroxyurea